Conjoined twins in the course of a triplet dichorionic diamniotic pregnancy - Młodawski, Jakub; Pliszka, Aleksandra; Mlodawska, Marta; Swiercz, Grzegorz (Medical Studies/Studia Medyczne, 2023)
Conjoined twins (CT) is an extremely rare complication in a monoamniotic twin pregnancy, affecting approximately 1 in 80,000 births. In our case report, we present the occurrence of this complication in a patient with a triple dichorionic pregnancy. The complication was diagnosed in the 15th week of pregnancy. The degree of organ connection in CT did not predict the survival of the conjoined foetuses after delivery. The third foetus was morphologically normal and had a separate chorion. The patient did not decide to undergo selective CT foeto-reduction in the second trimester. The natural course resulted in spontaneous intrauterine death of the affected foetuses in the 30th week of pregnancy, followed by spontaneous preterm labour in the 36th week of pregnancy. The description of the case along with photographic documentation allows the diagnosis, procedure, and the spontaneous course of pregnancy with such a complication to be traced. The attached discussion deals with similar descriptions of such rare cases in the literature and proceedings.